Description of collective nuclear dynamics by density functional theory with Skyrme forces - Nesterenko, V. O.; Kleinig, W.; Kvasil, J.; Vesely, P.; Reinhard, Paul-Gerhard; Novikov, A. S. (2nd International Conference on Current Problems in Nuclear Physics and Atomic Energy, NPAE 2008 - Proceedings, 2009)
Ability of the time-dependent density functional theory (TDDFT) with Skyrme forces to describe electric giant resonances (GR) is scrutinized within the self-consistent separable RPA (SRPA) method recently developed by our group. The isovector E1(T = 1) and isoscalar E2(T = 0) and E0(T = 0) GR are explored with different Skyrme forces. Both spherical and deformed nuclei in rare-earth, actinide and superheavy regions are considered. A special attention is paid to the role of time-odd densities in the Skyrme functional, which are known to restore Galilean invariance violated by velocity-dependent time-even densities. The tentative classification of Skyrme forces, based on the description of isovector GR with time-odd densities, is proposed. It is shown that inclusion of these densities leads to much closer results of different Skyrme forces for the E0(T = 0) and so for compressibility of finite nuclei. The systematic SRPA calculations with the force SLy6 demonstrate nice agreement with available experimental data for the isovector E1(T = 1) in rare-earth and actinide nuclei and high predictability of the model for superheavy elements. The structure of E1(T = 1) right flank is discussed and its enhanced vorticity is predicted.
CRIS-Team Scopus Importer:2023-07-24